KAJIAN PERUBAHAN STRUKTUR SOSIAL PEKERJA MIGRAN DI PABRIK KERUPUK DUA IKAN KOTA BENGKULU - Al Syahab, Muhamad; Heriyanti, Lesti (JURNAL ILMIAH IDEA, 2024)
This study aims to analyze the social changes experienced by migrant workers at the Dua Ikan Cracker Factory in Bengkulu City. The focus of this research is on migrant workers who come from West Java with Sundanese ethnicity. The research method used is qualitative with a case study approach. Data were collected through observation, in-depth interviews, and documentation. The results showed that migrant workers experience various social changes, both in terms of values, norms, and social interactions. These changes are influenced by factors such as adaptation to the new environment, integration with the local community, and efforts to achieve economic goals. Talcott Parsons' AGIL theory (Adaptation, Goal Achievement, Integration, and Latency) is used to analyze the dynamics of social change that occur. The conclusion of this study is that migrant workers successfully adapt to the new environment, despite facing challenges such as language and cultural differences. The social changes that occur have a positive impact on the lives of migrant workers, including improved economic welfare and social integration with local communities.